Phylogenetic relationships and divergence times of Charadriiformes genera: multigene evidence for the Cretaceous origin of at least 14 clades of shorebirds - Baker, Allan J (The Royal Society, 2007)
Comparative study of character evolution in the shorebirds is presently limited because the phylogenetic placement of some enigmatic genera remains unclear. We therefore used Bayesian methods to obtain a well-supported phylogeny of 90 recognized genera using 5 kb of mitochondrial and nuclear sequences. The tree comprised three major clades: Lari (gulls, auks and allies plus buttonquails) as sister to Scolopaci (sandpipers, jacanas and allies), and in turn sister to Charadrii (plovers, oystercatchers and allies), as in previous molecular studies. Plovers and noddies were not recovered as monophyletic assemblages, and the Egyptian plover Pluvianus is apparently not a plover. Molecular dating using multiple fossil constraints suggests that the three suborders originated in the late Cretaceous between 79 and 102 Mya, and at least 14 lineages of modern shorebirds survived the mass extinction at the K/T boundary. Previous difficulties in determining the phylogenetic relationships of enigmatic taxa reflect the fact that they are well-differentiated relicts of old, genus-poor lineages. We refrain from suggesting systematic revisions for shorebirds at this time because gene trees may fail to recover the species tree when long branches are connected to deep, shorter branches, as is the case for some of the enigmatic taxa.